PENENTUAN NILAI INTRINSIKSAHAM PT CIPUTRA PROPERTY TBK. UNTUK KEPENTINGAN PEMBELIAN KEMBALI/BUY BACK SAHAM - , Budi Prasodjo, Ir. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Basically, this research objected to estimating an intrinsic value of PT Ciputra Property Tbk. shares when buy back acted by using discounted cash flow method and relative valuation. This research also used data of PT Ciputra Property Tbk. financial statements during the last five years from 2007 until 2011. Analysis method of discounted cash flow conducted by: sales or earnings projection analysis, financial statement projection, free cash flow projection, discount rate determination and value estimation. Relative valuation started with searching similar company in the same field of industry, choosing and specifying appropriate ratio or multiples from similar companies. This Multiples used to convert a relevant book value variable from PT Ciputra Property Tbk. become an estimation of market value. Multiples or ratio which used were: PER (Price Earning Ratio), PBV (Price to Book Value) and P/S (Price to Sales Ratio). The result from this research by using discounted cash flow method obtained an intrinsic value estimation of PT Ciputra Property Tbk. share per 31 Desember 2011 range from Rp499 up to Rp577. Result by using relative valuation obtained the following result: for the estimation of stocks price per share PT Ciputra Property Tbk. by using PER equal to Rp366 using PBV ratio equal to Rp499 and using price to sales ratio equal to Rp172. The mean from this three method and added control premium equal to Rp499 per share. Meanwhile when we using discounted cash flow method we calculated to Rp444 and added control premium to Rp577 per share. Then we reconciled two approaches and noted at Rp546 per share. The company had buy back their shares along December 2011 within range Rp460 up to Rp505. Based on this both approaching and share buy back action, price of PT Ciputra Property Tbk. share at 31 December 2011 while noted at Rp 490 per share possibility of undervalued.